INTEGRASI MATERI PENDIDIKAN SEKS DALAM PELAJARAN FIQIH PADA SISWA MADRASAH TSANAWIYAH - Sukamti Sukamti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Sex education is a conscious and systematic effort, both in schools, families, and communities, to explain problems related to knowledge of organs and reproductive health, as well as instincts, and marriage to children so that sexual abuse and irregularities occur in the future. Students at the madrasah tsanawiyah level need to get greater attention to sex education because at this time children or students begin to enter the teenage phase. Sex education at this time is very important so that madrasah tsanawiyah students have a correct understanding of sex so that they do not fall into free sex, deviant sex, and sex crimes. This study uses qualitative methods and data collection techniques in the form of observation, interviews, documentation, news studies, study of research results, and theories related to sex education in madrasah students. The object of this study was Grade VII students of MTsN 2 Ogan Ilir with primary data sources (Waka 2 Ogan Ilir curriculum curriculum and Fiqh subject teachers) and secondary (scientific works, books, articles, newspapers, and journals relevant to this study) . The results of this study indicate that in class VII of MTsN 2 Ogan Ilir, the integration of sex education material in Fiqh lessons appears in the thaharah material which includes kinds of unclean, large and small hadast, features of aqil baligh, ablution, tayamum, and obligatory bathing (bathing janabat ) and discussed a little about matter away from adultery.